Characterization, optimization and emission analysis of manually-made charcoal dust briquettes with starch, paper and algae binders - George Lomunyak; Booker Osodo; Francis Njoka; Emmanuel Kombe (Heliyon)
Utilization of loose waste biomass such as charcoal dust remains popular in low-to mid-income countries due to increased energy demands, poverty and heighten efforts to mitigate climate change. This study sought to investigate the effects of starch, paper and algae binders on the physical, mechanical and combustion characteristics and emission levels of manually-made acacia charcoal dust briquettes. Acacia charcoal dust is collected and mixed with different binders at binder proportions of 10 %, 15 %, 20 %, 25 % and 30 % of the total weight for individual samples. Briquette samples are produced using a manually-operated briquetting machine. Briquettes are dried, characterized, and analyzed. Response Surface Methodology is used to investigate the effect of binder type and binder proportions on calorific value, ignition time and burning rate of the briquettes. Results show that the density of the produced briquettes from Charcoal-Starch (CS), Charcoal-Paper (CP) and Charcoal-Algae (CA) samples ranged between 571.5 kg/m3- 678.1 kg/m3, 495.8 kg/m3-534.4 kg/m3, 535.6 kg/m3-578.2 kg/m3, respectively. A mean shatter resistance of 91.3 %, 97.9 % and 95.2 % is obtained for CS, CP and CA briquettes, respectively. Moisture content, volatile matter, ash content and fixed carbon for all the samples ranged between 4.7 % and 7.1 %, 30 % and 46 %, 14 % and 32 %, 23 % and 56 %, respectively. Moreover, optimization response results show that a 30 % starch binder proportion gives the best calorific value, ignition time and burning rate. The highest emissions for CO, NOx and SO2 are, respectively, 389 ppm, 2.86 ppm and 2.26 ppm for CS samples, 345.3 ppm, 5.46 ppm, and 2.66 ppm for CP, and 422.1 ppm, 5.46 ppm 3.06 ppm for CA samples. Those results show that it is practically feasible to manually-make quality acacia charcoal dust briquettes with starch, paper and algae as binders. Such briquettes hence provide a quality source of fuel curbing deforestation and waste dumping, reducing fuel shortages in cities and forming a source of livelihood especially in developing countries.